A case of an extra-sensitive perception of ESP - Fadhil H.A.Y. Mansor, (Penerbit UKM, 2001)
Given the choice, many English language practitioners would rather not have anything to do with ESP. One of the oft-quoted reasons for this from instructors is that ESP can only be taught by those knowledgeable in the subject matter. Another reason relates to the question of methodology, whereby instructors, in trying to appear knowledgeable, often find themselves inadequate even in the role of pseudo-subject experts. As for course developers, selecting textbooks that are suitable for both homogeneous and heterogeneous classes can be almost impossible.